Evaluation of the Extraction Properties and Stability of Extracted Rare Earth Complexes in Ionic Liquid Extraction System Using β-Diketone. Issue 5 (28th July 2016) - Matsumiya, Masahiko; Yamada, Takahiro; Murakami, Sena; Kohno, Yuji; Tsunashima, Katsuhiko
ABSTRACT: The extraction behavior of rare earth (RE) species was investigated on benzoyltrifluoroacetone (Hbfa) /triethyl-pentyl-phosphonium bis(trifluoromethyl-sulfonyl)amide ([P2225 ][TFSA]) system in this study. The stoichiometry of the extracted complex shown RE: ligands = 1:3 by slope analysis regardless of the kinds of acid media in the aqueous phase. The extraction mechanism in this system was revealed as [RE 3+ ]aq + 3[Hbfa]IL [RE(bfa)3 ]IL + 3[H + ]aq and [TFSA] − anion did not participate in the extraction mechanism. The result of Raman spectroscopy also supported the stoichiometry of the extracted complex. Moreover, the chelate formation constant ( β ) of [Nd(bfa)3 ] and [Dy(bfa)3 ] was also evaluated by the direct measurement of [bfa] − anion by ion chromatography. The hypersensitive peak ( 4 I9/2 → 2 G7/2 *) in the UV-Vis-NIR spectrum also confirmed the formation of [Nd(bfa)3 ]. The average chelate formation constants (log β ) of [Nd(bfa)3 ] and [Dy(bfa)3 ] were estimated to be 7.58 and 7.93, respectively. The value of log β (Dy) was larger than that of log β (Nd); thus, this result indicates that [Dy(bfa)3 ] was more stable than [Nd(bfa)3 ]. Furthermore, the optimized structure of the extracted complexes – [Nd(bfa)3 (H2 O)3 ] and [Dy(bfa)3 (H2 O)2 ] – were also evaluated by the density functional theory (DFT) calculation. On the optimized geometries, the average bond length of the centered Nd 3+ ion or Dy 3+ ion against the O atom in the 1-carbonyl group was 2.728 Å or 2.407 Å, respectively. This result suggested that the Dy 3+ ion would be combined more strongly with the [bfa] − anion than the Nd 3+ ion.